Preparation of Pt catalysts supported on activated carbon felts (ACF) - de Miguel, Sergio Ruben (2002)
Activated carbon felts (ACFs) have been used as supports for Pt catalysts. The preparation was carried out by the impregnation method using chloroplatinic acid as metal precursor. The effect of impregnation time and surface chemistry of the support on the catalytic properties and the characteristics of the metallic phase have been investigated. Nitrobenzene (Nbz) hydrogenation in liquid phase at 25 °C and cyclohexane (CH) dehydrogenation in gas phase at 300 °C were used as catalytic tests. The state of platinum in reduced catalysts (at 100 and 350 °C) was studied by TPR and XPS. Oxygen surface groups only produce a slight effect on the catalytic properties. The use of low impregnation times (30 min) during the preparation of Pt/ACF leads to catalysts with Pt mainly deposited in the outer shell of the fibers, while at higher impregnation times, the metallic atoms seem to be deposited inside the pores. Pt(0) species appear in catalysts reduced at 100 °C by effect of the reducing properties of the carbon fiber exhibiting a considerable catalytic activity for Nbz hydrogenation.